818 Length of Hospital Stay (LOS) of Neonates Undergoing Surgery at a Tertiary Neonatal Unit. (October 2012) - Shetty, SK; Kennea, N; Giuliani, S; Desai, P; Richards, J
Abstract : Background and Aims: Detailed length of stay (LOS) data for infants following surgical procedures are important for prediction of neonatal resources and helpful when counselling parents following a new diagnosis. There are few recent data available on LOS for different surgical conditions in the literature, and none describing a range of procedures from one centre. Objective: To describe LOS for common surgical procedures in a single centre tertiary referral neonatal unit. Methods: Data were collected for a 5-year period. If babies were transferred to another unit following surgery, these units were contacted to determine total LOS. We included babies that had surgery during their first admission to our unit and who survived to discharge. Results: Conclusion: Our data for length of stay LOS for following neonatal surgery compare favourably to historical data. Our data show a wide variation in lengths of stay; we believe that median LOS with ranges will enable us to give more detailed information to families at diagnosis. These data allow more detailed planning of resource allocation when planning admissions of these often complex babies.